Editor’s Remarks - Bajunid, Siti Farhana (Journal of Research Management and Governance, 2024)
It is our distinct pleasure to welcome you to the latest issue of the Journal of Research Management and Governance (JRMG). As we navigate an increasingly challenging research landscape, the importance of effective research management has never been more apparent.